RERANGKA KERJA KONSEPTUAL UNTUK MEMBANGUN DAN MEMELIHARA KEUNGGULAN BERSAING YANG BERKELANJUTAN - Joseph L.Eko Nugroho (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2004)
Sustainable Competitive Advantage (SCA) was one of the issues that's been a controversial between theorist and practitioneer. All the effort that companies do should not based only in one perspective. This paper try to combine three perspective regarding to SCA. The colaboration between this three perspective should give clear definition and understanding about SCA and resulting in perfection of its framework.